1997
DOI: 10.1097/00006123-199712000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment of Brain Abscess in Patients with Congenital Cyanotic Heart Disease

Abstract: Our findings suggest that IVROBA strongly influences poor outcome in patients with cyanotic heart disease. The key to decreasing poor outcomes may be the prevention and management of IVROBA. To reduce operative and anesthetic risk in these patients, abscesses should be managed by less invasive aspiration methods guided by computed tomography. Abscesses larger than 2 cm in diameter, in deep-located or parieto-occipital regions, should be aspirated immediately and repeatedly, mainly using computed tomography-gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
24

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 30 publications
1
59
0
24
Order By: Relevance
“…Marnelak et al proposed to introduce the drainage and antibiotics to the abscess diameter >2.5 cm [10]. Mikihiko et al suggested that the abscess in the diameter of >2 cm, deep abscess or posterior cranial fossa should be repeatedly punctured to reduce the intracranial pressure and prevent cerebral abscess from entering the ventricle [11]. It is difficult to be effective the drainage of the abscess by only puncture and drainage the abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Marnelak et al proposed to introduce the drainage and antibiotics to the abscess diameter >2.5 cm [10]. Mikihiko et al suggested that the abscess in the diameter of >2 cm, deep abscess or posterior cranial fossa should be repeatedly punctured to reduce the intracranial pressure and prevent cerebral abscess from entering the ventricle [11]. It is difficult to be effective the drainage of the abscess by only puncture and drainage the abscess.…”
Section: Discussionmentioning
confidence: 99%
“…12,23,57 Transposition of great vessels, tricuspid atresia, pulmonary stenosis, and double-outlet right ventricle have also been reported as predisposing factors. 12,56,57 Most of these abscesses are supratentorial in location. 23,49,56 Because most of these patients present only with headache, the threshold for performing a CT scan in a patient with cyanotic heart disease should be low.…”
Section: Cyanotic Heart Disease and Brain Abscessmentioning
confidence: 99%
“…These low-perfusion areas commonly occur in the junction of gray and white matter, and they are prone to seeding by microorganisms that may be present in the bloodstream. 28,56 The hematogenous mode of spread accounts for the subcortical location as well as the multiple number of abscesses often encountered in these patients. 7,12,22,57 Streptococcus milleri was the most common organism isolated from the abscess in patients with cyanotic heart disease in one series.…”
Section: Cyanotic Heart Disease and Brain Abscessmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain abscess is a frequent complication in patients with congenital heart disease [1]. The reported incidence of brain abscess in patients with cyanotic heart disease is 5 -18.7 %with cerebellar abscess comprising 6-35 % of all brain abscesses.…”
Section: Introductionmentioning
confidence: 99%